Analisis Penerapan Kurikulum 2013 Ditinjau dari Preofesionalisme Guru di Sekolah Dasar - Mustakim Mustakim; Nur Linda (Program Studi PGSD Universitas Madako Tolitoli, 2022)
This study aims to know the professionalism at SDN 2 Tolitoli. This type of research is a qualitative research, where in collecting data using observation, interview, and documentation technique. The data analysis technique used is data reduction, data presentation, conclusion drawing and verification. Indicator of teacher professionalism at SDN 2 Tolitoli can be implemented well if viwed from the indicators, namely the teacher is able to develop responsibilities as well as possible, the teacher is able to carry out his role seccesfully, the teacheris able to work in an effort to achive educational goals, and the teacher is able to carry out role in the learning and teaching process in the classroom. Of the four indicators can be implemented well, this can be see from the success of teacher in implementing the 2013 curriculum so far this is done with ful responsibility